PRODUKSI GLUKOSA DARI JERAMI PADI (Oryza sativa) MENGGUNAKAN JAMUR Trichoderma sp. - Yuli Rismawati; Syaiful Bahri; Prismawiryanti Prismawiryanti (KOVALEN: Jurnal Riset Kimia, 2016)
Research glucose production from rice straw (Oryza sativa) using Trichoderma sp. has conducted. This study aime is to determine the effect konsentrasi Trichoderma sp. And a straw fermentation of rice (Oryza sativa) against production. Research glucose levels was done using a completely randomized design (CRD) with factorial pattern 4 variation of the concentration of Trichoderma sp. (0%, 24%, 36% and 48%) and fermentation time (3, 4, 5and6 weeks), glucose levels were analyzed using DNS with UV-Visible spectrophotometry. The measurement results showed that the highest glucose levels obtained at various concentration Trichoderma sp. 36% fermentation time during the five week sthat is equal to 14.525%. There is a positive interaction between the concentration of Trichoderma sp. and the fermentation time, the best combination of time and fungal concentration of 5 weeks and 36%, respectively.Keywords : Rice straw, Trichoderma sp., Fermentation, DNS, Spectrophotometer Uv-Visibel, Glucose.